Comparison of Shared Reading versus Emergent Reading: How the Two Provide Distinct Opportunities for Early Literacy. (2nd May 2013) - Curenton, Stephanie M.; Kennedy, Symonne
Abstract : This study examined mother-child interactions across two types of reading interactions—shared reading versus emergent reading—in order to determine (a) if mothers and children provide the same amount of language input across the two interactions, (b) if the socioemotional quality is consistent across the interactions, and (c) if the language input and socioemotional quality across the two interactions are differentially associated with children's scores on early literacy assessments. Twenty-five mother-child dyads participated in both interactions. Children were given a standardized test of early reading and an emergent reading score based on a rubric designed particularly for the book they were reading. Results indicated that during the shared reading mothers provided more language input (i.e., they talked more), but children increased their amount of talk during the emergent reading, making such input effects null. Overall, socioemotional quality was consistent across the two interactions, except mothers provide more literacy feedback during shared reading. Both language input and socioemotional quality were associated with higher scores on early literacy assessments, but the contribution of these factors varied depending across the type of reading interaction. Results are discussed in terms of education implications for literacy practices at home and school.